UNDERSTANDING THE COLLETION AND DISTRIBUTION OF ZAKAT DURING COVID-19 PANDEMIC - Syafaat Muhari (Universitas Wahid Hasyim, 2023)
This research is expected to be able to provide a good understanding of the behavior of zakat collection from the public and how zakat institutions distribute the zakat. This study uses a quantitative method using panel data and samples from five zakat institutions in Indonesia, such as the National Zakat Agency (Baznas), Rumah Zakat, Rumah Yatim, Dompet Dhuafa, and Inisiatif Zakat Indonesia. Furthermore, the ZIS collection and distribution data that will be analyzed is annual data for the period 2018 to 2021. The results of this study show that the performance of ZIS collection has continued to show a positive trend during covid-19 pandemic, which indicates that ZIS receipts from muzakki are not affected by economic conditions. However, there have been a number of changes of ZIS distribution because it need to prioritize asnaf of fakir, misin, and fisabilillah in order to recover economic conditions due to Covid-19.